Mężczyzna po tuningu. Działania jako manifestacja operatywności. (Zdjęcie jako narzędzie autokreacji) = The male after tuning: actions as a manifestation of efficiency (a picture as a tool for auto-creation) - Leszkowicz-Baczyńska, Żywia (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The deliberations undertaken in the article are a fragment of a broader research project into the social and cultural position of the modern male. This issue poses the question about the extent and activity areas in which men presenting themselves relate to traditional characteristics of the personal model of the male, and those in which one can find new elements brought about by contemporary social, economic and cultural reality.
Keywords: mężczyzna; autokreacja; operatywność; socjologia wizualna; fotografia; analiza socjologiczna